2017
DOI: 10.1136/oemed-2016-104178
|View full text |Cite
|
Sign up to set email alerts
|

Pleural abnormalities in the Framingham Heart Study: prevalence and CT image features

Abstract: Background The prevalence of pleural abnormalities in the general population is an epidemiologically important index of asbestos exposure, which has not been investigated since a radiography-based study in 1980. Methods We examined 2633 chest CT scans (mean 59.2 years, 50% female) from the Framingham Heart Study (FHS) for the presence and image characteristics of pleural plaques and diffuse pleural thickening. Demographics and pulmonary function were stratified by the presence of pleural abnormalities in ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…OSHA's earliest limits were set “primarily to protect employees against asbestosis.” Its 1986 determination concluded that reducing the PEL to 0.2 f/cc would reduce the asbestos cancer mortality risk from lifetime exposure to 7 deaths per 1000 workers, and the incidence of asbestosis to 5 cases per 1000 workers . Although the prevalence of chest radiographic findings among the post‐1973 cohort is low compared with the earlier cohorts, it is also higher than what is found in the general population, leading us to conclude that asbestos‐related disease has not yet been eliminated in exposed populations in the United States.…”
Section: Discussionmentioning
confidence: 75%
“…OSHA's earliest limits were set “primarily to protect employees against asbestosis.” Its 1986 determination concluded that reducing the PEL to 0.2 f/cc would reduce the asbestos cancer mortality risk from lifetime exposure to 7 deaths per 1000 workers, and the incidence of asbestosis to 5 cases per 1000 workers . Although the prevalence of chest radiographic findings among the post‐1973 cohort is low compared with the earlier cohorts, it is also higher than what is found in the general population, leading us to conclude that asbestos‐related disease has not yet been eliminated in exposed populations in the United States.…”
Section: Discussionmentioning
confidence: 75%
“…Since the prevalence of pleural plaques varies widely between studies, our findings must be considered alongside evidence from other epidemiological studies. In one such study, the reported prevalence of pleural abnormalities, pleural plaques and diffuse pleural thickening was 1.5% among 2633 chest CTs taken between 2009 and 2011 in the United States 19) . That study considered a general population of white, middle-class Americans, compared to our study of Japanese lung cancer patients, and included a younger age group (59.2±12.1 years compared to 71.3±9.9 years) and a higher proportion of females (50.3% compared to 27.6%).…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the comments by Franzblau et al 1 on our recent article ‘Pleural abnormalities in the Framingham Heart Study: prevalence and CT image features’ 2. Our study described CT image findings of pleural abnormalities including pleural plaques and pleural thickening in the Framingham Heart Study.…”
mentioning
confidence: 80%